41.5: Research on Trends and Solutions of Module Production Line Operation Mode in Semiconductor Display Industry. (26th August 2021) - He, Tao; Chu, Zhengyong; Niu, Lina; He, Dingfei; Guo, Xin; Pang, Yan; Gao, Rong; Zhang, Pu; Tian, Zengkui
Abstract : The purpose of this paper is to study and analyze the competitiveness of the current management mode of AMOLED module factories in the semiconductor display industry represented by BOE in China, and to analyze the global top enterprises in the same industry and the electronics manufacturing industry such as TSMC and other top enterprises in the world., which are the benchmark enterprises with advanced management. From several dimensions of management, field management system design, knowledge management and talent training system, front‐line employee compensation and promotion mode, combined with the characteristics of industry product life cycle, combing and summarizing the application scheme to improve enterprise management ability and talent training ability. At the same time, through intelligent data systems, ergonomic automation precision replacement equipment and other innovative solutions to optimize personnel efficiency. A new competitive model with technological innovation and management efficiency as the twin props has been developed to change the old model of low profit in traditional Chinese OEM manufacturing which relies on cheap labor cost.